Analysis of the Influence of Service Marketing Mix on Customer Purchase Decisions Mediated by Trust in JNE Medan Main Branch - Mesra B; Muhammad Toyib Daulay; Nur Fatiha Utami Nasution (International Journal of Management, Economic and Accounting, 2024)
The study analyzed the influence of the service marketing mix with variables assessed as Product (X1), Promotion (X2), Price (X3), Location (X4), Employee (X5), Physical Evidence (X6), and Process (X7) on the purchase decision (Y) of customers mediated by Trust (Z) at JNE Main Branch. The population in this study is 5,400 consumers with a sample size of 185 consumers. The research was conducted from August to October 2023. This study uses quantitative data processed by the SEM-PLS analysis method using SmartPLS 3.0 software. The data sources used are primary data taken directly from respondents and secondary data obtained from interviews with JNE Main Branch management. The results of the study show that the service marketing mix has a positive and significant effect on customer trust. This concludes that the service marketing mix consisting of products, places, promotions, places, employees, physical evidence, processes, and intervening variables, namely customer trust, has a positive and significant effect on purchase decisions and customer trust to use the services of JNE Medan Main Branch. The managerial implication of this study is the need for JNE Medan Main Branch to continue to improve the service marketing mix strategy, especially in terms of product quality, competitive pricing, ease of access, effective promotion, service quality, process efficiency, and the provision of attractive physical evidence. This is important to build customer trust and ultimately improve the purchase decision of freight forwarding services.